Exploring the barriers and facilitators of dietary self-care for type2 diabetes: a qualitative study in Ghana - Martin Hushie (Tabriz University of Medical Sciences, 2019)
Background: There is an increasing prevalence of type 2 diabetes (T2D) globally and countries in Sub Sahara Africa, such as Ghana are contending with the epidemic. The main objective ofthis study was to explore the barriers and facilitators of T2D self-care as perceived by patients and health providers (HPs) in Ghana. Methods: A maximum variation sample of 33 adult patients with a range of demographic features, diabetic conditions and self-care regimens and 3 providers were purposely selected from thespecialist diabetes clinic of a private hospital in Accra, Ghana. Data were collected using in depth interviews, which were recorded and transcribed; and non-participant observational fieldnotes-that were analyzed thematically through directed content analysis. Results: The findings reveal that T2D adult patients face many inter-related challenges to diabetes self-care, than enabling factors that fell into four major domains:1) the counselling process and context (patients missing follow-up appointments, unacceptance of diagnosis); 2)recommended food and diet regimens (changing habitual diets, dislike and confusion about recommended diets); 3) social aspects (social functions interfering with dietary regimens, family members diverting patient from dietary goals) and 4) fears (non-disclosure to family member/pretense of being well). Conclusion: Integrated self-management interventions are needed to address these barriers, including tailoring dietary education to patients' specific needs, guiding patients on how tomanage diet during social occasions and among family members; and as well, providing mental health support. Future research should focus on T2D self-care behaviours and practices outside the clinic, including home, work and shopping environments.